Juvenile court in the school-prison nexus: youth punishment, schooling and structures of inequality. Issue 3 (27th May 2022) - Goldman, Margaret; Rodriguez, Nancy
ABSTRACT: Influenced by Dr. Michael Leiber, a body of juvenile justice research explores how legal, extralegal and institutional decision-making factors racialize the process of punishment. While this scholarship has indirectly considered the role of school-related factors for unequal court outcomes, an interdisciplinary body of work explores the relationship between schooling and criminal justice institutions directly, often under the framework of the school-to-prison pipeline . Building on juvenile justice research, and departing from the pipeline framing, we utilize the analytic framework of the school-prison nexus – which theorizes schools and the criminal justice system as fundamentally and symbiotically linked – to examine the role of school referral source and school enrollment status on differential court outcomes. Our findings highlight the structural and institutional processes behind the relationship between school enrollment and incarceration, and have implications for the ways in which the nexus between schools and juvenile courts entrench broader systems of inequality.